Structural and electrochemical investigation of LiNi0.8Co0.2-xMxO2 (M = Al, Al plus Mg, Al plus Mg plus Fe) synthesized by solid-state method - Sethuprakhash, V.; Basirun, Wan Jefrey (Springer Verlag (Germany), 2008)
Lithium nickel cobalt oxide materials doped with Al, Mg, and Fe were synthesized by solid-state reaction at 800 degrees C for 18 h to study the effects of adding transition and nontransition metals to the structure. Crystalline compounds were obtained as revealed by powder X-ray diffraction (XRD). Energy dispersive analysis of X-rays (EDAX) was used to determine the elemental ratio of all the samples. Impedance measurements showed that all samples have decreasing conductivities at higher temperatures and gave negative activation energies. The addition of nontransition metals actually decreased the conductivities of the materials.